A generic mechanism in Neisseria meningitidis for enhanced resistance against bactericidal antibodies. - Uria, M; Zhang, Q; Li, Y; Chan, A; Exley, R; Gollan, B; Chan, H; Feavers, I; Yarwood, A; Abad, R; Borrow, R; Fleck, R; et al. (2008)
The presence of serum bactericidal antibodies is a proven correlate of protection against systemic infection with the important human pathogen Neisseria meningitidis. We have identified three serogroup C N. meningitidis (MenC) isolates recovered from patients with invasive meningococcal disease that resist killing by bactericidal antibodies induced by the MenC conjugate vaccine. None of the patients had received the vaccine, which has been successfully introduced in countries in North America and Europe. The increased resistance was not caused by changes either in lipopolysaccharide sialylation or acetylation of the alpha2-9-linked polysialic acid capsule. Instead, the resistance of the isolates resulted from the presence of an insertion sequence, IS1301, in the intergenic region (IGR) between the sia and ctr operons, which are necessary for capsule biosynthesis and export, respectively. The insertion sequence led to an increase in the transcript levels of surrounding genes and the amount of capsule expressed by the strains. The increased amount of capsule was associated with down-regulation of the alternative pathway of complement activation, providing a generic mechanism by which the bacterium protects itself against bactericidal antibodies. The strains with IS1301 in the IGR avoided complement-mediated lysis in the presence of bactericidal antibodies directed at the outer membrane protein, PorA, or raised against whole cells.